The Influence Of Motivation And Discipline On The Performance Of PT Employees. Sanbe Farma Cimareme - Puspita Hasri; Makmur Makmur (Jurnal Scientia, 2024)
Finding out how motivation and discipline affected the employees' productivity at PT Sanbe Farma Cimarene was the aim of this study. The sample employed in this inquiry consisted of thirty responders from among all employees. In this study, descriptive and associative methods of data collection are employed through the use of a questionnaire. Multiple linear regression was employed in this study's data analysis using the SPSS software, version 22 for Windows. The results of the study indicate that the independent variables of discipline (X2) and motivation (X1) have a substantial impact on employee performance (Y) (F test), and these variables have a significant impact on employee performance in part (t test).